Qualitative Assessment of Digital Forensic Tools - Singh, Sakshi; Kumar, Suresh (Asian Journal of Electrical Sciences, 2020)
Forensic science is a study of science to criminals and civil laws. Digital forensics is the part of forensic science relating to proof found in computers and advanced storage media. Forensic examiners gather, protect and break down logical confirmations over the span of examination. Digital information contains data as content, pictures, sound, video and so on. These days numerous cybercrime cases, for example, hacking, banking cheats, phishing, email spamming, etc., have developed which are connected with a computerized information. Since the digital investigation is turning into an expanding concern, numerous digital forensic tools have been created to manage the difficulties of exploring computerized wrongdoings. The motivation behind digital forensics strategies is to look, protect and extract data on advanced frameworks to discover potential confirmations to exhibit them in the courtroom. In this paper, we have discussed five kinds of forensics namely Network Forensics, Live Forensics, Cyber Forensics, Database Forensics, and Mobile Forensics. The paper depicts a list of digital forensic tools in detail and looks at them based on the characterized parameters to figure out which tool suits better for any investigation. The paper looks at network, database and mobile forensic tools and examines the silent features and uniqueness of each of the tools along with their functionalities.